THE GROWTH AND YIELD OF SWEET POTATO TREATED WITH DIFFERENT SEEDLINGS AND CHICKEN MANURE AGAINST CYLAS FORMICARIUS TUBER DAMAGE - Triyono, Kharis; Asrori, Ahmad; Mustofa, Fajar Arif (jfpublisher, 2023)
Sweet potato is a well-known food crop in Indonesia and has become an alternative substitution for rice. This research was conducted to obtain information on the effect of chicken manure doses and seed types on tuber damage by boleng pests in sweet potato plants. The research was conducted in Dayu village, Gondangrejo, Karanganyar from April to July 2022. The research was arranged using a factorial Randomized Complete Block Design (RCBD), consisting of two treatment factors, such as the type of seedlings (B1 seedlings in the shoot section 25 cm, B2 seedlings in the stem section 25 cm) and the dose of chicken manure (K0: 0, K1: 11.25, K2: 21.25, K3: 31.25, K4: 41.25 gr per plant) each treatment combination was repeated three times. Parameters observed were intensity of pest attack, the total of healthy tubers per plant, the total of boleng tubers per plant, fresh weight of tubers per plant and fresh weight of boleng tubers per plant. The results indicated that the treatment of seedling types, doses of chicken manure and their interactions did not have a significant effect on all parameters observed, the highest amount of healthy tubers per plant was 8.3 in treatment B1K2 (the use of shoot seedlings and doses of chicken manure 21.25 grams per plant) and the highest fresh weight of tubers per plant was 810 grams in treatment B1K1 (the use of shoot seedlings and doses of chicken manure 11.25 grams per plant).